Optimism of Guidance and Counseling Students in Completing Thesis - Siti Azizah Fauzia Fiqri; Yusri Yusri (Universitas Negeri Padang, 2020)
Optimism is a tendency to expect the best results and always think positive when dealing with certain situations. Optimism helps individuals to face the obstacles that appear in achieving goals. This research aim to describe the optimism of guidance and counseling students in completing thesis in terms of aspects permanence, pervasive, and personalization. This research uses quantitative methods with a descriptive type. The populations of this study were 191 students of Guidance and Counseling, Faculty of Education, Padang State University who worked on their thesis. The total of sample of 131 students was selected using the Stratified Random Sampling technique. The research used a questionnaire instrument with Likert scale models. Data were analyzed by descriptive statistical analysis. The results of the study revealed the optimism of students on; (1) optimism of guidance and counseling students in completing thesis overall they’re in a high category with a percentage 47,33%, (2) optimism of guidance and counseling students in completing thesis based on the permanence aspect is in a high category with a percentage 48,09%, (3) optimism of guidance and counseling students in completing thesis based on pervasive aspect is in high enough category with a percentage 51,15%, (4) optimism of guidance and counseling students in completing thesis based on personalization aspect is in high enough category with a percentage 49,62%. Based on the research findings, it is suggested to the counselor in guidance and counseling services unit (UPBK) to be able to support and provide appropriate counseling services to optimize students optimism and to solve students problems related to the process of completing thesis.